2006
DOI: 10.1073/pnas.0602702103
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential family members PKD1L3 and PKD2L1 form a candidate sour taste receptor

Abstract: Animals use their gustatory systems to evaluate the nutritious value, toxicity, sodium content, and acidity of food. Although characterization of molecular identities that receive taste chemicals is essential, molecular receptors underlying sour taste sensation remain unclear. Here, we show that two transient receptor potential (TRP) channel members, PKD1L3 and PKD2L1, are coexpressed in a subset of taste receptor cells in specific taste areas. Cells expressing these molecules are distinct from taste cells hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
444
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(477 citation statements)
references
References 47 publications
15
444
3
4
Order By: Relevance
“…It has been previously shown that the sweet receptor is a heterodimer of T1R2 and T1R3 (17,18), that the umami receptor is a heterodimer of T1R1 and T1R3 (17,19), and that the bitter receptors are a family of T2R receptors (20,21). The epithelial sodium channel (22) and transient receptor potential family members PKD1L3 and PKD2L1 (23) are plausible candidates as receptors for the salty and sour (acid) tastes, respectively. A common characteristic of kokumi taste substances such as GSH is that they are tasteless by themselves but enhance basic tastes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the sweet receptor is a heterodimer of T1R2 and T1R3 (17,18), that the umami receptor is a heterodimer of T1R1 and T1R3 (17,19), and that the bitter receptors are a family of T2R receptors (20,21). The epithelial sodium channel (22) and transient receptor potential family members PKD1L3 and PKD2L1 (23) are plausible candidates as receptors for the salty and sour (acid) tastes, respectively. A common characteristic of kokumi taste substances such as GSH is that they are tasteless by themselves but enhance basic tastes.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies indicate that polycystin-1 proteins are components of mechanosensory or chemosensory signal transduction mechanisms (4,5). In the renal tubule epithelium Pkd1 is located in the primary cilium and acts as a fluid flow sensor (6,7), whereas Pkd1l3 is associated with sour taste transduction (8,9). In contrast, the functions of other family members are poorly understood.…”
mentioning
confidence: 99%
“…PKD1L3 and TRPP3 (PKD2L1) have been shown to form heteromeric channels in sensory taste receptor cells and may contribute to sour taste transduction (Ishimaru et al 2006). It is attractive to speculate that the parallel rise in expression that we note here may indicate an interaction between PKD1L3 and TRPP3 in the cochlea that gives rise to physiologically significant aspects of cochlear function.…”
Section: Trp Subunits With No or Little Expression And/or No Distinctmentioning
confidence: 75%